PENGARUH GAYA MENGAJAR GURU KEWIRAUSAHAAN TERHADAP MOTIVASI BELAJAR SISWA KELAS XI JURUSAN MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS (MPLB) DI SMKN 1 JENEPONTO - Hadaniah; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the impact of Entrepreneurship Teachers’ Teaching Style on Students’ Learning Motivation among Grade XI students of the Office Management and Business Services (MPLB) program at SMKN 1 Jeneponto. Entrepreneurship is a core subject in the vocational curriculum and plays an important role in developing students’ innovative, creative, and independent abilities. Student learning outcomes are strongly influenced by external factors, including teachers’ teaching styles and students’ motivation. This research uses a quantitative approach with a correlational research design. The population of this study consists of all Grade XI MPLB students at SMKN 1 Jeneponto, totaling 75 students, with a sample of 45 students selected using simple random sampling. Data were collected through questionnaires distributed to the students. The data analysis techniques include simple linear regression, F-test, and t-test. Further discussion concludes that there is a strong correlation and a positive influence of teachers’ teaching style on students’ learning motivation at SMKN 1 Jeneponto, in line with previous research findings. The better the teacher’s teaching style, the higher the students’ learning motivation. Keywords: Teaching Style, Student Learning Motivation, Entrepreneurship, Simple Linear Regression